"Because they want to teach you about their culture": Analyzing effective mentoring conversations between culturally responsible mentors and secondary science teachers of indigenous students in mainstream schools. Issue 10 (10th April 2015) - Tolbert, Sara
Abstract Te Kotahitanga is an educational reform project in Aotearoa/New Zealand demonstrated to have significantly impacted the participation, achievement, and retention of indigenous Māori students in secondary schools. In this paper, I share results from a study of culturally responsible mentoring at 4 different schools participating in the Te Kotahitanga reform project. Specifically, I investigated how Te Kotahitanga facilitators (i.e., site‐based mentors/instructional coaches) engage novice and experienced science teachers in reflective conversations around culturally sustaining science instruction for indigenous students. I identify four key themes from these mentoring conversations that can serve as a useful framework for culturally responsible mentoring in science. © 2015 Wiley Periodicals, Inc. J Res Sci Teach 52: 1325–1361, 2015.